SISTEM INFORMASI PEMINJAMAN BUKU BERBASIS WEBSITE DIPERPUSTAKAAN (STUDI KASUS SMP N 1 KEDAWUNG) - Anjarwati, Jesika; Imaduddin, Helmi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
School libraries are crucial for supporting student learning and literacy. However, manual library management at SMP Negeri 1 Kedawung leads to various challenges, such as recording errors, late reporting, and a lack of service efficiency. This study aims to develop a website-based book lending information system to address these challenges. The development method used is the Waterfall model, which consists of analysis, design, implementation, testing, and maintenance. The system was built using the PHP programming language with the Laravel framework and a MySQL database, and was designed to be accessible to three user roles: admin, staff, and students. The implementation results show that the system is able to manage book, user, borrowing, returning, and reporting data in a more structured and efficient manner. System testing was conducted using the Black Box method to directly test system functions, and the System Usability Scale (SUS) to assess user ease of use. From 30 respondents, an average SUS score of 80 was obtained, indicating that the system falls into the